Municipal business relations and the emergence of a development state in South Africa - Ditlhage, Goodwill Gabriel (My University, 2018)
Successful East Asian developmental states achieved remarkable growth in a short space of time. They intervened in their economies and also built constructive relations with business and the capitalists class. South Africa has similarly committed itself to building a developmental state and its local governments have a developmental mandate. However, local governments in South Africa suffer from a plethora of problems. In the constellation of local governments, cities occupy a different position and possess the potential to play a developmental role. The City of Johannesburg is one such city. Its developmental approach including its effort to build relations with business since the dawn of the democratic era, are examined in this thesis. The results present a mixed picture. While positive city-business relations existed, these were not deeply embedded. This was epitomised by the lack of pervasive city-wide feelings of developmental solidarity and narrow agendas that animated city-business relations. However, in line with developmental state theory, especially the twenty-first century kind that not only focuses on growth but also redistribution, the city managed to make certain positive strides. On the anti-developmental side though, the quality of its business-related growth-enhancing services such as investment-attraction lagged behind. Unlike East Asian developmental states, the city also appeared to lack the ability to significantly determine the direction of development, especially investment by the private sector. Overall, the case of Johannesburg reveals the difficulty of emulating East Asian developmental states, especially the challenge of forging lasting city-business relations against the backdrop of informal segregation and huge inherited disparities.
Thesis submitted to the Department of Political Studies, University of the Witwatersrand in fulfilment of the requirements for the Degree of Doctor of Philosophy, 2018
Keywords: Economic development-South Africa; Local government-South Africa; South Africa-Economic conditions; South Africa-Social conditions-21st century